Influence of Pos Giro Mobile (PGM) in Running the Service Process of PT. Pos Indonesia (Case Study at Padangsidimpuan Post Office) - Ayu Widyastuti Rafisa; Halimah Safitry Al-Fauziah; Nurbaiti Nurbaiti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Along with the rapid development of technology, business people are required to be able to use the internet as a medium for doing business online in order to increase service effectiveness so that customers can access services easily anywhere and anytime. This study aims to analyze how the role of Pos Giro Mobile (PGM) in carrying out the service process of PT. Indonesian post. The research method used is descriptive by examining what are the benefits and how to introduce PGM to the community as well as what obstacles are passed. The results showed that PT. Pos Indonesia has introduced the Pos Giro Mobile (PGM) product to the public. However, people who lack knowledge of technology become one of the obstacles so that PT. Pos Indonesia decided to socialize directly as well as teach how to use the application.